2022
DOI: 10.3390/ma15144834
|View full text |Cite
|
Sign up to set email alerts
|

Structure Characterization and Impact Effect of Al-Cu Graded Materials Prepared by Tape Casting

Abstract: With the need of developing new materials, exploring new phenomenon, and discovering new mechanisms under extreme conditions, the response of materials to high-pressure compression attract more attention. However, the high-pressure state deviating from the Hugoniot line is difficult to realize by conventional experiments. Gas gun launching graded materials could reach the state. In our work, the corresponding Al-Cu composites and graded materials are prepared by tape casting and hot-pressing sintering. The mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Few other works examined the acoustic impedance, residual stresses, and corrosion wear. 4,30,31 To the best of authors knowledge, no work was reported on tribological properties of Al-Cu FGM. Thus, present work is an attempt made to explore the erosion wear and abrasive wear behavior of Al-Cu MFGM fabricated through PM.…”
Section: Introductionmentioning
confidence: 99%
“…Few other works examined the acoustic impedance, residual stresses, and corrosion wear. 4,30,31 To the best of authors knowledge, no work was reported on tribological properties of Al-Cu FGM. Thus, present work is an attempt made to explore the erosion wear and abrasive wear behavior of Al-Cu MFGM fabricated through PM.…”
Section: Introductionmentioning
confidence: 99%